Structure construction materials: casting and strength of concrete arch pan - Wan Zarriqbar Hakim , Wan Hilmi (2013)
Nowadays, the methods and the cost of constructions rapidly changes parallel to the current technological development. Due to the increase of the materials cost in the construction, new types of construction methods have been introduced. Permanent formwork is one of the methods that is used to reduce the wastage and construction cost. The advantage of the permanent formwork is where the formwork will become a part of the structure. This research is to determine the optimal height of arch pan under uniformly distributed load from the slab and to achieve the required load of 100kg or 1 000N of concrete arch pan without cracking. The construction process is important in order to produce the standard quality with preferable size of the arch pan formwork. Plastic meshes and plastic netting were laid inside along the length of the concrete arch pan which acts as a flexural reinforcement. Based on the arch pan design calculation, it shows that the maximum height of the arch pan is 75mm and the required load for the concrete arch pan has successfully passed without cracking. The strength of concrete arch pan increases with the use of plastic mesh and plastic netting as a reinforcement.